Studies on ultra high performance concrete incorporating copper slag as fine aggregate. (15th February 2015) - Ambily, P.S.; Umarani, C.; Ravisankar, K.; Prem, Prabhat Ranjan; Bharatkumar, B.H.; Iyer, Nagesh R.
Highlights: Alternate aggregate system for ultra high performance concrete (UHPC). Complete replacement of natural aggregate by waste copper slag in UHPC. Optimization of granular mixture by suitable separation and particle packing. Abstract: This paper investigates the technical feasibility of using copper slag as fine aggregate replacement in ultra high performance concrete (UHPC). The studies demonstrated that it is possible to produce UHPC having compressive strength greater than 150 MPa by incorporation of copper slag. The complete replacement of standard sand by copper slag resulted in a maximum decrease in 28-day compressive strength of about 15–25% whereas, the flexural strength, fracture energy recorded was of the similar order. It can be concluded from the results that use of copper slag as fine aggregate in UHPC is technically viable.